2022
DOI: 10.3389/fpls.2022.991114
|View full text |Cite
|
Sign up to set email alerts
|

Sex-based metabolic and microbiota differences in roots and rhizosphere soils of dioecious papaya (Carica papaya L.)

Abstract: Dioecious plant species have a high genetic variation that is important for coping with or adapting to environmental stress through natural selection. Intensive studies have reported dimorphism morphism in morphology, physiology, as well as biotic and abiotic stress responses in dioecious plants. Here, we demonstrated the dimorphism of metabolic profile and the preference of some microorganisms in the roots and rhizosphere soils of male and female papaya. The metabolic composition of roots were significantly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…It would be similarly interesting to analyze the effects of sexual dimorphism in secreted antibacterial compounds on stress response, fitness, or physiological differences in C. purpureus male and female strains. Another implication of our study is that if genetic variation in secreted antibacterial compounds can also be demonstrated for C. purpureus male and female strains in their natural habitats, R40- and GG1-associated microbiomes could also be different, as was recently demonstrated for roots and rhizosphere soils of the dioecious flowering plant Carica papaya [ 36 ].…”
Section: Discussionmentioning
confidence: 59%
“…It would be similarly interesting to analyze the effects of sexual dimorphism in secreted antibacterial compounds on stress response, fitness, or physiological differences in C. purpureus male and female strains. Another implication of our study is that if genetic variation in secreted antibacterial compounds can also be demonstrated for C. purpureus male and female strains in their natural habitats, R40- and GG1-associated microbiomes could also be different, as was recently demonstrated for roots and rhizosphere soils of the dioecious flowering plant Carica papaya [ 36 ].…”
Section: Discussionmentioning
confidence: 59%
“…Differences in the physical and chemical traits of the litter or the quality and quantity of root‐deprived compound profiles can lead to divergent microbial communities (Palomino et al., 2023; Zhalnina et al., 2018). Males and females show differences in physical and chemical traits during leaf growth (Guo et al., 2022; Zhang et al., 2014; Zhou et al., 2022), and also different in nutrient resorption efficiency during leaf senescence (Yu, Huang, et al., 2022). The results implied that the leaf litter traits of males and females are different and they may influence microbial communities during the decomposition stage, which would be another interesting topic but not investigated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Plants interacting with different neighbors have been shown to induce major changes in soil microbial communities (Guo et al, 2019). Recent studies found that males and females can recruit sex-specific soil microbial communities (Guo et al, 2021(Guo et al, , 2022Vega-Frutis & Guevara, 2009;Zhou et al, 2022;Zhu et al, 2024), which would in turn affect soil nutrient availability and plant growth (Guo et al, 2023). Alterations in belowground interactions between male and female plants or between the same sex plants might further cause important changes in the structure and function of bacterial and fungal communities.…”
Section: Stronger Intra-than Intersexual Competition Of Populus Catha...mentioning
confidence: 99%